Digital Dashboard Transformation as a Mediator Between Service and Content Delivery and Sustainable Performance in Islamic Educational Institutions in Indonesia - Gatot Kunta Kumara; Agus Rahayu; Lili Adi Wibowo; Rasto Rasto (Jurnal Pendidikan Terapan, 2026)
Purpose: This study examines the mediating role of Digital Dashboard Transformation (DDT) in the association between Service and Content Delivery (SCD) and Sustainable Performance (SP) in Islamic educational institutions in Indonesia. Methods: A quantitative cross-sectional design was employed involving 104 respondents selected through purposive sampling from Islamic educational institutions that had implemented digital-based educational and administrative services. Data were collected using a 36-item questionnaire measured on a seven-point Likert scale. Construct reliability and validity were assessed using Composite Reliability (CR) and Average Variance Extracted (AVE). The mediating role of DDT was evaluated using bias-corrected bootstrapping with 5,000 resamples. Findings: The results indicate that SCD was positively associated with DDT, and DDT was positively associated with SP. The indirect effect of SCD on SP through DDT was statistically significant, supporting a complementary partial mediation mechanism. The bootstrap analysis showed that the 95% bias-corrected confidence interval for the indirect effect did not include zero (LLCI = [isi nilai], ULCI = [isi nilai]). The model explained 50.5% of the variance in SP (R² = 0.505), suggesting that SCD and DDT are important factors associated with sustainability outcomes in Islamic educational institutions. Research implications: The findings suggest that strengthening service and content delivery may support the development of dashboard-based monitoring capabilities, which are associated with improved sustainability-related outcomes. Educational institutions may benefit from integrating digital dashboard systems to support evidence-based decision-making and organizational performance monitoring. Originality: This study contributes to the digital transformation and sustainability literature by examining DDT as a mediating mechanism linking SCD and SP within Islamic educational institutions. The findings provide empirical evidence of an indirect association between digital service capabilities and sustainability outcomes in a faith-based educational context, while acknowledging the limitations of cross-sectional data for causal inference.